The Changing Face Of Australia - "Richardson, Margat"; Margot Richardson (London Hodder Wayland, 2005)
This series examines different countries and how their political, social, and economic conditions have changed throughout the nation's history. Each book offers a firsthand insight into how each nation is changing to meet the challenges of the 21st century. Every title is packed with brilliant photographs, clear diagrams, informative website addresses, and a glossary. A concise illustrated overview for young readers depicting changes in Australia in the early 21st century, featuring photographic depictions, literary notes, and an index.
Includes photographs by Chris Fairclough; contains literature references and index.